Performance Assessment and Calibration of Low-cost Moisture Sensors at Multiple Oxisol Depths (Research, Society and Development, 2022)
Monitoring of soil moisture is a key component in irrigation management and can be carried out with the aid of low-cost electromagnetic sensors. This study aimed to develop calibration equations for the HFM2030 sensor at different depths (0-20; 20-40; 40-60; 60-80; 100 cm) of Oxisols and to assess the accuracy levels of calibration equations used in the continuous monitoring of soil moisture. Reference values of soil moisture content were measured by a standard gravimetric method, converted to volumetric moisture, and then compared with sensor readings to develop calibration equations. The fit of the regression function was evaluated based on the determination coefficient (R2). The results indicated that the calibration equations were linear at different soil depths. Calibrating the HFM2030 sensor improved the estimate of volumetric water content by 31.21%, 23.46%, 24.93%, 31.93%, and 41.18% in the 0-20, 20-40, 40-60, 60-80 and 80-100 cm layers, respectively. Here, it is demonstrated that the correct calibration of HFM2030 should precede the installation and use of these sensors in the field. The results of this study represent another step toward the development of criteria aiming for greater precision in the use of sensors in irrigation management. The calibration equations developed in this study can be applicable and useful for farmers and researchers working with HFM2030 sensors in similar soil conditions in other regions of Brazil and globally.